Simulation of a Secondary Settler Based on Sedimentation Curves (Hungarian Journal of Industry and Chemistry, 2010)
The settlers of wastewater treatment plants are of the same importance as the activated sludge tanks. This role manifests in the course of simulating wastewater treatment systems as well. Several models describing the process of sedimentation were developed of which the one-dimensional models dividing the settlers into given layers are wide-spread. In this paper the parameter dependence of the Takács-model was studied. Samples were taken from the wastewater arriving to the secondary settler at different times in order to determine the settling profiles belonging to different concentrations. The Vesilind function and the maximum practical settling velocity were derived base on these data. Using three sets of measurement data the Takács model was fitted by modifying certain parameters. The simulation results gave an overestimation on the concentrations of the effluent in all three cases and there were differences of a few percents in the lowest layer as well. Taking the changes in the order of magnitude of the suspended solids concentration into consideration in the process of sedimentation i.e. it had to be decreased from 4000–6000 g/m3 to 8–12 g/m3 the higher values in the effluent layer are acceptable until they are below the permissible limit.
Keywords: settling velocity; Takács-model; wastewater; Vesilind-function